Digitising Complex Data: Integrating Text, Images and Physical Organisation - Ore, Espen S. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The National Library of Norway (NLN) is the Norwegian national deposit library and has a history going back to 1815 when national library functions were taken care of by The University of Oslo Library. In 1989 the Rana Division of the National Library was established and given the responsibility for the administration of the Norwegian arrangement of legal deposit. In 1992 the Norwegian Parliament decided to establish a unified self-contained National Library with its main office located in Oslo. The Office of the National Librarian came into operation in 1994. The Oslo Division (NLN-O) was established in 1999 based on national functions and collections separated from the University of Oslo Library.